Características sócio-demográficas das puérperas e seguimento da gravidez: o que mudou em 17 anos? - Vera Santos; Márcio Moura; João Paulo Pinto; Vítor Almeida; José Maio (Acta Médica Portuguesa, 2012)
In recent years, the time for motherhood has been postponed, which is related to social aspects and can lead to health problems for the pregnant women and the child. An appropriate follow-up of the pregnancy is essential for identification and early treatment of possible complications. The purpose of this study was to evaluate some social and demographic characteristics and the pregnancy follow-up among puerperas, in two different times separated by 17 years (1991 e 2008). In this study, we found that the birth of a first child occurs now later, is more planned and happens more frequently outside of marriage. The postponement of motherhood can be associated with an increased rate of miscarriages. There has been a decrease in the rate of induced abortions, which is probably the result of the implementation of strategies for family planning. We noticed a decline in the number of pregnancies that had not a proper follow-up, demonstrating the improvement of health care. The immigrant population is responsible for about one quarter of the births in the Algarve, with a higher percentage of unplanned pregnancies, which eventually might be related to socio-economic vulnerabilities, but no difference was found in the surveillance of pregnancy, demonstrating a good accessibility of this population to health care. It is essential the existence of information about the risks of a late pregnancy and of social infrastructures to support motherhood at younger ages. Pregnancy surveillance programs have been successful, but there are still gaps in obstetric monitoring. Despite good results in terms of surveillance of pregnancy, the immigrant population may present some vulnerabilities, which means that their access to maternal and child health care should be monitored.